Goffmans totalinstitution set i en dispositivoptik - Hamre, Bjørn (Psyke & Logos, 2015)
The starting point of this article is a questioning of Erving Goffman’s total institution as a concept that has mainly focused on an internal perspective on the logics of the institution. Thus there is a risk of under emphasizing how the internal dynamics are influenced by various social, political and economic forms of rationality that affects the institution’s internal logics and social practices. The article argues that such an analysis can be made by using Michel Foucault’s term dispositive. The dispositive offers an analysis of how the function of the total institution changes over time and how social rationales affect the institution’s internal power technologies and the construction of the subject. Based on three dispositives, the dispositive of discipline, the dispositive of security and the dispositive of governmentality, the article demonstrates how such an analysis can be approached. The article provides examples of how different dispositive analyzes have been approached.